Proportion of SARS‐CoV‐2 positive tests and vaccination in Veterans Affairs Community Living Centers. Issue 8 (4th May 2021) - Rudolph, James L.; Hartronft, Scotte; McConeghy, Kevin; Kennedy, Michael; Intrator, Orna; Minor, Lisa; Hubert, Terrence L.; Goldstein, Mary K.
Abstract: Background/Objectives: COVID‐19 has caused significant morbidity and mortality in nursing homes. Vaccination against SARS‐COV‐2 holds promise for reduction in COVID‐19. This operational analysis describes the proportion of SARS‐COV‐2 positive tests before, during, and after vaccination. Design: Retrospective longitudinal cohort analysis from October 1, 2020 until February 14, 2021. Setting: A total of 130 Department of Veterans Affairs (VA) Community Living Centers (CLC), analogous to nursing homes. Intervention: Vaccination for SARS‐CoV‐2. Measurements: The primary measure is the proportion of SARS‐CoV‐2 positive tests among CLC residents. In a pooled analysis of weekly testing and vaccine data, the proportion of positive tests was compared for the unvaccinated, first dose, and second dose. For each CLC, we identified the week in which 50% of CLC residents were vaccinated (index week). The analysis aligned the index week for CLCs and examined the proportion of SARS‐CoV‐2 positive tests at the CLC level before and after. As a reference, we plotted the proportion of positive tests in nursing homes in the same county as the CLC using publicly reported data. Results: Within the pooled VA CLCs, the first SARS‐CoV‐2 vaccine dose was delivered to 50% of CLC residents within 1 week of availability and second dose within 5 weeks. Relative to the index week, the risk ratio of SARS‐CoV‐2 positive tests in the vaccinated relative to unvaccinated was significantly lower in Week 4 (relative risk 0.37, 95% confidence interval 0.20–0.68). Throughout the study period, the proportion of SARS‐CoV‐2 positive tests in community nursing homes was higher compared to VA CLC and also declined after vaccine availability. Conclusion: The proportion of SARS‐CoV‐2 positive tests significantly declined in VA CLCs 4 weeks after vaccine delivery and continued to decline in vaccinated and unvaccinated residents. The results describe the importance of SARS‐CoV‐2 surveillance and vaccination in VA nursing home residents. Abstract : See related editorial by Ouslander et al and related articles by Mor et al, Moore et al, and Domi et al . in this issue.